Origin, synchronization, and propagation of sleep slow waves in children - Castelnovo, Anna; Lividini, Althea; Riedner, Brady A.; Avvenuti, Giulia; Jones, Stephanie G.; Miano, Silvia; Tononi, Giulio; Manconi, Mauro; Bernardi, Giulio (NeuroImage (Orlando, Fla.), 2023)
•Slow-wave origin and distribution are more posterior and asymmetric in children than in young adults.•Slow-wave amplitude is larger and globality is lower in children than in young adults.•Slow-waves with different synchronization efficiency undergo distinct maturational changes.•The observed changes may reflect the maturation of local and long-range connections.•Slow-wave-related indices may allow to track physiological and pathological development. Sleep slow wave activity, as measured using EEG delta power (<4 Hz), undergoes significant changes throughout development, mirroring changes in brain function and anatomy. Yet, age-dependent variations in the characteristics of individual slow waves have not been thoroughly investigated. Here we aimed at characterizing individual slow wave properties such as origin, synchronization, and cortical propagation at the transition between childhood and adulthood. We analyzed overnight high-density (256 electrodes) EEG recordings of healthy typically developing children (N = 21, 10.3 ± 1.5 years old) and young healthy adults (N = 18, 31.1 ± 4.4 years old). All recordings were preprocessed to reduce artifacts, and NREM slow waves were detected and characterized using validated algorithms. The threshold for statistical significance was set at p = 0.05. The slow waves of children were larger and steeper, but less widespread than those of adults. Moreover, they tended to mainly originate from and spread over more posterior brain areas. Relative to those of adults, the slow waves of children also displayed a tendency to more strongly involve and originate from the right than the left hemisphere. The separate analysis of slow waves characterized by high and low synchronization efficiency showed that these waves undergo partially distinct maturation patterns, consistent with their possible dependence on different generation and synchronization mechanisms. Changes in slow wave origin, synchronization, and propagation at the transition between childhood and adulthood are consistent with known modifications in cortico-cortical and subcortico-cortical brain connectivity. In this light, changes in slow-wave properties may provide a valuable yardstick to assess, track, and interpret physiological and pathological development.